Severity of SARS-CoV-2 infection in a hospital population: a clinical comparison across age groups - Chiara Rosazza; Laura Alagna; Alessandra Bandera; Arianna Biffi; Fabiana Ciciriello; Andrea Gramegna; Vincenzina Lucidi; Paola Giovanna Marchisio; Paola Medino; Antonio Muscatiello; Sara Uceda Renteria; Carla Colombo (BMC, 2023)
Abstract Background Children tend to have milder forms of COVID-19 than adults, however post-acute complications have been observed also in the paediatric population. In this study, we compared COVID-19-related outcomes and long-term complications between paediatric and adult patients infected by SARS-CoV-2. Methods The study is based on individuals enrolled from October 2020 to June 2021 in the DECO COVID-19 multicentre prospective study supported by the Italian Ministry of Health (COVID-2020-12371781). We included individuals with RT-PCR -confirmed SARS-CoV-2 infection, who were evaluated in the emergency department and/or admitted to COVID-dedicated wards. The severity of SARS-CoV-2 infection was compared across age groups (children/adolescents aged < 18 years, young/middle-aged adults aged 18-64 years and older individuals) through the relative risk (RR) of severe COVID-19. Severity was defined by: 1) hospitalization due to COVID-19 and/or 2) need or supplemental oxygen therapy. RR and corresponding 95% confidence intervals were estimated using log-binomial models. Results The study included 154 individuals, 84 (54.5%) children/adolescents, 50 (32.5%) young/middle-aged adults and 20 (13%) older adults. Compared to young/middle-aged adults the risk of hospitalization was lower among paediatric patients (RR: 0.49, 95% CI: 0.32-0.75) and higher among older adults (RR: 1.52, 95% CI: 1.12-2.06). The RR of supplemental oxygen was 0.12 (95% CI: 0.05-0.30) among children/adolescents and 1.46 (95% CI: 0.97-2.19) among older adults. Three children developed multisystem inflammatory syndrome (MIS-C), none was admitted to intensive care unit or reported post-acute Covid-19 complications. Conclusions Our study confirms that COVID-19 is less severe in children. MIS-C is a rare yet severe complication of SARS-CoV-2 infection in children and its risk factors are presently unknown.